A fluorometric method for the determination of 2-deoxy- d-glucose - Blecher, Melvin (Analytical biochemistry, 1961)
1. 1. A fluorometric assay for 2-deoxy- d-glucose (DoG) is described which is based upon the fluorescence of 2-(1-glycerol)-5-carboxy-7-aminoquinoline, the reaction product of the condensation of deoxyglucose with 3,5-diaminobenzoic acid. The quinoline derivative is maximally excited at about 405 mμ and has an emission maximum at about 495 mμ. 2. 2. Fluorescence is proportional to concentration of DoG between 2.8 and 125 mμmoles/ml solution. The method is highly reproducible and precise. 3. 3. With the fluorometric method, small amounts of DoG can be determined accurately in the presence of very high concentrations of glucose. Interference due to high concentrations of deoxyribose is small, and that due to tissue components is non-existent. DoG can be quantitatively recovered from tissue homogenates by extraction with trichloroacetic acid. 4. 4. The same reaction, upon which is based the fluorometric assay, can also be used for the colorimetric estimation of DoG. However, the colorimetric method is insensitive to low concentrations of DoG, has a low degree of reproducibility and precision, and is subject to serious interference by glucose and deoxyribose.